Effects of flow patterns and salinity on water holdup measurement of oil-water two-phase flow using a conductance method. (November 2016) - Liu, W.X.; Jin, N.D.; Han, Y.F.; Zhai, L.S.; Chen, X.; Zhang, H.X.
Highlights: Vertical upward oil-water two-phase flow with different salinities is investigated. Measurement deviations of water holdup under different salinities and flow patterns are analyzed. The dependence of holdup measurement accuracy on the salinity and reference resistance is studied. Experimental flow patterns are identified using recurrence plot algorithm. Abstract: This research investigates the effects of flow pattern and salinity of oil-water two-phase flow on water holdup measurement using a conductance method. Firstly, vertical upward oil-water two-phase flow experiment is conducted in a 20 mm inner diameter (ID) pipe, in which the salinities of aqueous solutions are set as 151 ppm, 1003 ppm, 2494 ppm and 4991 ppm respectively. Experimental water-cut and mixture velocity are set as 80–100% and 0.0184–0.2576 m/s. In the experiment, three different flow patterns, i.e., dispersed oil-in-water slug flow (D OS/W), dispersed oil-in-water flow (D O/W) and very fine dispersed oil-in-water flow (VFD O/W) are observed and recorded by a high speed camera. Meanwhile, we collect the response of Vertical Multiple Electrode Array (VMEA) conductance sensor excited by a sine voltage signal. The result shows that, for VFD O/W, the water holdup from VMEA sensor shows a satisfied agreement with that of quick closing valve (QCV) method under certain salinities, i.e., 1003 ppm as well as 2494 ppm. For D OS/W flow and D O/W flow characterized by dispersed oil droplets with various sizes, considerable deviations of water holdup between VMEA sensor and QCV method under four kinds of salinity aforementioned are presented. Afterward, according to experimental analysis along with theoretical deviation, it is concluded that the deviation of the measurement system reaches its minimum when reference resistance in the measurement circuit and salinity of the aqueous solution satisfy constraint conditions, and the accuracy of water holdup using the conductance method can be improved through adjusting reference resistance to match the salinity of water phase. Finally, the recurrence plot algorithm is utilized to identify typical flow patterns mentioned above and it shows satisfied results on comprehending the discrepancies among different flow patterns, demonstrating that the recurrence plot algorithm can be effectively applied in flow pattern identification regarding oil-water flows.